(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence and genetic spectrum of ESBL, AmpC, and carbapenemase genes in Escherichia coli isolated from inpatients at Nguyen Tri Phuong Hospital, and to assess the association between these genes and phenotypic resistance to third- and fourth-generation Cephalosporins and Carbapenems. Methods: We conducted a cross-sectional descriptive study on 141 E.coli isolates recovered from clinical specimens of inpatients between March 2024 and June 2025. Antimicrobial susceptibility testing was performed according to CLSI M100 (2025). ESBL genes (CTX-M groups), AmpC genes (CIT, DHA, CMY, etc.), and carbapenemase genes (NDM, OXA-48, etc.) were detected using multiplex real-time PCR. Results: The proportions of ESBL- and AmpC-producing isolates were 57.4% and 9.9%, respectively; no isolate simultaneously displayed ESBL (+) and AmpC (+) phenotypes. CTX-M9-type genes predominated over CTX-M1, while DHA and CIT/CMY were the main AmpC genes. Carbapenemase genes were detected in 5.7% of isolates (NDM and OXA-48), all as single carbapenemase genes. Isolates carrying ESBL and/or AmpC genes showed high resistance to third- and fourth-generation Cephalosporins, whereas Imipenem resistance was observed only in carbapenemase-producing isolates. Conclusions: Inpatient E.coli isolates at this hospital exhibit a high burden of ESBL and plasmid-mediated AmpC, with predominance of CTX-M9-type genes and the early emergence of NDM/OXA-48. These findings underscore the need for ongoing molecular surveillance and prudent β-lactam use.